Tc-99m MDP Bone SPECT/CT Findings of a Patient Detected with a New Mutation in LEMD3 Gene: A Case of Osteopoikilosis - Silov, Güler (Mol Imaging Radionucl Ther, 2018)
Osteopoikilosis is an inherited condition with autosomal dominant trait resulting in sclerotic foci throughout the skeleton. It has been suggested that loss-of-function mutations of LEMD3 gene located on 12q14.3 result in osetopoikilosis. A bp heterozygote deletion was detected in our patient at the cytosine nucleotide at position 1105 with molecular genetic analysis. Although this mutation has not been previously described, it was considered to be the most likely cause of the disease in our patient due to frame shift and premature stop codon formation. As in our case, three phase bone scintigraphy and whole body imaging did not reflect the true extent of lesion sites and lesion activity. SPECT/CT images could reflect lesion location and activity more accurately, and could be a good alternative for differential diagnosis of unexplained bone pain and sclerotic lesions in one examination.